PENERAPAN ASSESSMENT KINERJA PADA MATA KULIAH DASAR-DASAR TEKNOLOGI PENDIDIKAN PROGRAM STUDI TEKNOLOGI PENDIDIKAN - Prabowo, Mulyo (MAJALAH ILMIAH PEMBELAJARAN, 2006)
This research had a purpose to know whether assessment of achievement (Performance Assessment) was the evaluation implement that comprehensive and as reflection means that could identify the student’s capacity in the process of the receipt, the implementation of knowledge and skills in the subject of the foundations of Educational Technology. This research was the research of the class action that took place two cycles. In each cycle was given by the task, afterwards was evaluated and be compared to the results to see the achievement as well as it’s change. The analysis of the data by making use of the quantitative approach afterwards be interpreted qualitatively. This research was carried out by three person, one of among them at the same time as the teacher. Participants in this subject total 29 first semester students, who were divided into two groups; namely the group with the odd and even task. From results of the analysis of the data and it’s discussions, then could be concluded that assessment of achievement (Performance Assessment) gave several functioning benefits as follows: 1) to describe the achievement of the student who helped the lecturer in giving the value of the end that only did not have a basis in results of the exam; 2) as the reflection implement that gave the picture comprehensive concerning the achievement of the student. From results of this conclusion, then was suggested that the use assessment the achievement better be used for the specific tasks, in a sense had the criterion and the aspect that were evaluated clearly.